Socioeconomic characteristics and quality parameters of chilled raw milk produced in Santa Maria, RS, Brazil (Research, Society and Development, 2021)
The present study evaluated socioeconomic aspects of milk producing farms, characterizing the production and quality of milk from small and medium farms in the rural area of ​​the municipality of Santa Maria / RS. The study was carried out in three stages: I. Georeferencing of the target properties of the study; II. Visit and application of the information collection instrument; III. Determination of quality parameters of chilled raw milk through physical-chemical and microbiological analyzes, including density, protein content, defatted dry extract (ESD), lactose and ash, standard plate count (CPP). It was observed that milk production in the municipality of Santa Maria is concentrated in two main macro-regions. It was possible to verify vulnerabilities in reproductive management, the predominant production system and control of reported health problems, hindering maximum efficiency. Milk losses occur in 13 of the 30 rural establishments. In relation to market share, rural producers were classified into groups considering the destination of production (direct or for industry), technological level (technically or low-tech) management adopted on the properties (systems of cow breeding, milking and conservation of raw milk). The principal component analysis (PCA) showed little association between technological level and physical-chemical quality of milk. In general, the milk samples from the evaluated properties reached the minimum requirements recommended by Brazilian legislation for chilled raw milk.